2002
DOI: 10.1097/00001648-200207000-00016
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette Smoking and the Risk of Mucinous and Nonmucinous Epithelial Ovarian Cancer

Abstract: Cigarette smoking appears to be a risk factor for mucinous but not for nonmucinous tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
39
1
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 28 publications
8
39
1
1
Order By: Relevance
“…Although many studies in the literature claimed that cigarette smoking was associated with an increased risk for ovarian cancers, especially mucinous epithelial ovarian cancer. [16][17][18] Goodman and Tung reported that active tobacco smoking was not a risk factor for invasive ovarian cancer. 19 In a recent large population study, epithelial ovarian cancer did not observe an association with smoking.…”
Section: Discussionmentioning
confidence: 99%
“…Although many studies in the literature claimed that cigarette smoking was associated with an increased risk for ovarian cancers, especially mucinous epithelial ovarian cancer. [16][17][18] Goodman and Tung reported that active tobacco smoking was not a risk factor for invasive ovarian cancer. 19 In a recent large population study, epithelial ovarian cancer did not observe an association with smoking.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies [7][8][9]11,12,15 in the review 6 also suggest that smoking may have a promoting effect regarding the development of mucinous tumors because of the short period of smoking exposure before diagnosis. Furthermore, Jordan et al, discuss the possibility that the revealed increased risk may be due to misclassification of mucinous tumors from the gastrointestinal tract, pancreas or cervix that present clinically as primary ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Jordan et al found that there was a significant doubling in risk of mucinous, but not of serous, endometroid and clear cell ovarian cancers among current smokers compared to never smokers. 6 This meta-analyses included data from 1 cohort study, 7 8 population based case-control studies [8][9][10][11][12][13][14][15] and 1 pooled analysis of 10 case-control studies from the US. 16 Because the use of tobacco is rising sharply globally, 17 smoking may generate large numbers of ovarian cancers if a causal association exists.…”
mentioning
confidence: 99%
“…Whether the risk of other subtypes of ovarian cancer might also be influenced by cigarette smoking is less certain, as prior studies have not been uniform in their findings (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14).…”
mentioning
confidence: 99%